Human rights protection in land acquisition in forest areas for infrastructure projects - Ilham Desri Satria (PT WIM Solusi Prima, 2026)
This study examines the implications of Forest Area Use Approval (PPKH) in land acquisition for the Bakauheni–Terbanggi Besar Toll Road project with particular attention to the protection of property rights and Economic, Social, and Cultural Rights (ESCR). The research is motivated by the legal conflict arising from the overlap between forestry law and land law regimes, which creates uncertainty for individuals holding legally registered Freehold Title (Hak Milik) over land subsequently designated as forest areas. Employing a socio-legal approach, this study combines statutory analysis, field observation, and document review to assess the legal and social consequences of the PPKH mechanism. The findings demonstrate that the application of PPKH to land already certified under Freehold Title generates legal dualism between state control over forest areas and the recognition of private property rights under the national land law system. This situation weakens property rights protection, limits access to fair compensation, and adversely affects the livelihoods of agrarian communities whose economic and social well-being depend on land ownership and use. Furthermore, the study finds that the current implementation of PPKH does not adequately safeguard human rights, particularly the rights to property, work, and an adequate standard of living. The research concludes that converting forest areas into Other Land Use Areas (APL) prior to land acquisition provides a more appropriate legal framework by ensuring greater legal certainty, enhancing compensatory justice, and strengthening human rights protection within the implementation of national strategic infrastructure projects.